Changes in electrostatic surface potential of Na+/K+-ATPase cytoplasmic headpiece induced by cytoplasmic ligand(s) binding - Kubala, Martin; Grycova, Lenka; Lansky, Zdenek; Sklenovsky, Petr; Janovska, Marika; Otyepka, Michal; Teisinger, Jan (Biophysical journal, 2009)
A set of single-tryptophan mutants of the Na(+)/K(+)-ATPase isolated, large cytoplasmic loop connecting transmembrane helices M4 and M5 (C45) was prepared to monitor effects of the natural cytoplasmic ligands (i.e., Mg(2+) and/or ATP) binding. We introduced a novel method for the monitoring of the changes in the electrostatic surface potential (ESP) induced by ligand binding, using the quenching of the intrinsic tryptophan fluorescence by acrylamide or iodide. This approach opens a new way to understanding the interactions within the proteins. Our experiments revealed that the C45 conformation in the presence of the ATP (without magnesium) substantially differed from the conformation in the presence of Mg(2+) or MgATP or in the absence of any ligand not only in the sense of geometry but also in the sense of the ESP. Notably, the set of ESP-sensitive residues was different from the set of geometry-sensitive residues. Moreover, our data indicate that the effect of the ligand binding is not restricted only to the close environment of the binding site and that the information is in fact transmitted also to the distal parts of the molecule. This property could be important for the communication between the cytoplasmic headpiece and the cation binding sites located within the transmembrane domain.
Keywords: povrchové vlastnosti; Acrylamide; adenosintrifosfát; sodíko-draslíková ATPasa; mutace; ligandy; akrylamid; jodidy; Ligands; Static Electricity; hořčík; Magnesium; Iodides; molekulární modely; Fluorescence; Models, Molecular; Animals; cytoplazma; Cytoplasm; Sodium-Potassium-Exchanging ATPase; konformace proteinů; statická elektřina; zvířata; Surface Properties; myši; Adenosine Triphosphate; Protein Conformation; Mutation; Mice; fluorescence